Cerebral control of speech and limb movements - Hammond, Geoffrey R., 1945- (Advances in psychology (Amsterdam, Netherlands), 1990)
Discussed in this book is the association between speech and movements, especially those of the preferred hand. Both are skilled motor activities that appear to depend upon a similar neural organization that is available in the left hemisphere of the brain. The nature of this association of the cerebral control of speech and skilled manual performance is discussed in four sections: 1. Motor control and speech examines speech as a motor activity; 2. Language and gesture examines the correspondence between spoken language and manual gesture; 3. Motor performance and aphasia examines the motor impairments associated with aphasias; 4. Interactions of speech and manual performance examines the interactions that occur between concurrent verbal and manual activities.